Determination of optimal dietary calcium levels under different zinc sources in Jing Tint 6 layer chicks from hatch to day 14 - Chengyan Gong; Hongpeng Shi; Shuan Liu; Xinyi Gao; Shoujun Zhang; Hao Liu; Dan Wan; Yulong Yin (Animal Nutrition, 2025)
An experiment was conducted to investigate the optimal dietary calcium (Ca) levels in Jing Tint 6 layer chicks fed different sources of zinc (Zn). A total of 1440 day-old birds with similar body weight (38 ± 0.5 g) were selected and divided into 10 groups with 6 replicates per group, each containing 24 chicks. The experimental period lasted from hatch to d 14. Diets were formulated to contain 2 sources of Zn: organic Zn (80 mg/kg Zn as hydroxy methionine Zn, HMZn) and inorganic Zn (80 mg/kg Zn as Zn sulfate). For each Zn source, 5 diets were formulated with Ca levels of 0.80%, 0.90%, 1.03%, 1.10%, and 1.20%, respectively. The results showed that dietary Ca significantly increased the average daily gain (ADG) (P < 0.001). In addition, ADG was enhanced by the supplementation of organic Zn compared to diets containing inorganic Zn (P = 0.009). Tibia length was significantly increased by the interaction of Ca and Zn (P = 0.038). Serum Ca and P levels were significantly higher in the group supplemented with organic Zn compared to the group fed inorganic Zn (P < 0.05). The apparent total tract retention coefficients (ATTRC) of Ca increased quadratically with the increase of Ca level (P < 0.001). The excreta Ca levels decreased in the group supplemented with organic Zn compared to the group fed inorganic Zn (P < 0.001). The optimal dietary Ca levels were estimated as 0.90%, 0.86% and 0.96% for birds fed organic Zn and 0.91%, 0.92% and 1.06% for birds fed inorganic Zn using non-linear models based on the criteria of ADG, tibial length, and ATTRC of Ca, respectively. In conclusion, supplementing with organic Zn enhanced the growth performance of birds and reduced their calcium requirements from hatch to d 14.